Storm Runoff Pollution from a Residential Catchment in Miri, Sarawak - Ho, Carrie Lee Ing; Quan, Choo Bo (Curtin University Sarawak Malaysia, 2012)
In this paper, stormwater runoff from a residential catchment located in Miri, Sarawak was characterized to determine the pollutant concentrations and loading. The observed average event mean concentration were 116 mg/L for TSS, 115 mg/L for COD, 1.5 mg/L for NH3-N, and 0.23 mg/L for Pb. Based on the Interim National Water Quality Standards (INWQS) for Malaysia, the average EMC value for TSS exceeded class II (50 mg/L), exceeded class V (>100 mg/L) for COD, and exceeded class III (0.9 mg/L) for NH3-N. All four water quality parameters exhibited first flush characteristic, but to varying magnitude and was influenced by the storm characteristics.